Smart contracts: It’s rules and jurisprudence - Al-Omari, Sumaia Ali (Journal of Islamic Sciences, 2022)
This study aimed to clarify the smart contracts, which mean " Meeting the acceptance of the contractors through special softwires, in the form of encrypted codes, under the contractors conditions, their rights and obligations arising from each of them, and they are implemented automatically within specific legally acceptable controls", its important characteristics and challenges, and closely related words, in addition to mentioning the importance jurisprudential controls that must be available in the contract formula, both contracting parties, and subject of contracts.One of this study importance was the applicability of the contract pillars theory to these contracts, which means ruling on its permissibility and arranging all the implications of traditional contracts of obligation and commitment, if the aforementioned jurisprudential controls are adhered to, and the study recommends the need for jurisprudential councils to adopt this ruling, and to benefit from the experiences of some countries that activated these contracts in all fields, which constituted a qualitative leap in people's lives.
Keywords: smart contracts; blockchain; ethereum; code